A proposta de reforma do ensino jurídico em Chaïm Perelman e reflexões sobre sua aplicação no Brasil - Lourenço, Ricardo Alves Barreira (2011)
The objectives of the present essay is to examine the thought of Chaim Perelman studying his proposal of modification of the Belgian law education and, therefore, reflect on its viability in Brazil. In a report sent to the seminar held in Perugia, Italy, in 1973, Perelman takes over his thoughts on the study of rhetoric applied to law and proposes the revision of its teaching system in Belgium. In this exposition, we seek to understand the proposal within the author's thought and also comprehend his critics to the logic applied by the Exegesis School, by the legal positivism and natural law dogmatic. For this, we reconsider the historic journey of rhetoric and also of the rational-deductive doctrine in the study of law. In order to allow the transposition of Perelman ideas to Brazil, a picture of the standards that guide Brazil`s current law education is drawn and, at last, we go through ideas about the conviniency and/or possibility of implementing the reform proposed by the author in the Brazilian system. We conclude, finally, that the study of rhetoric and argumentation has much to contribute to the current perspective of law education in Brazil